The potential of invasive species Praxelis clematidea extract as a bioherbicide for Asystasia gangetica - TRIMURTI HESTI WARDINI; INAS NUHA AFIFA; RIZKITA RACHMI ESYANTI; NOVI TRI ASTUTININGSIH; HIDAYAT PUJISISWANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wardini TH, Afifa IN, Esyanti RR, Astutiningsih NT, Pujisiswanto AH. 2023. The potential of invasive species Praxelis clematidea extract as a bioherbicide for Asystasia gangetica. Biodiversitas 24: 4738-4746. The occurrence of weeds in agriculture directly impacts crop productivity, and the reliance on synthetic herbicides to solve the problem has raised concerns about the increasing environmental damage. Using bioherbicides to control weeds is necessary to reduce the negative impact of synthetic herbicides. Bioactive compounds derived from plants can be utilized to develop eco-friendly herbicides. Praxelis clematidea extract was reported to exhibit allelopathic activity against weeds. This study aims to evaluate the potential of P. clematidea extract as a bioherbicide to control seed germination and seedling growth of Asystasia gangetica weed. P. clematidea water extract was screened for its chemical compounds and determined its phytotoxic effects on Asystasia gangetica. The results showed that P. clematidea water extract contained phenolics, alkaloids, and terpenoids. P. clematidea extract suppressed seed germination, the time needed for seed germination, sprout length, number of leaves, biomass, and total chlorophyll contents. LC50values for the seed germination, seedling, root, and shoot growth were calculated at 9%, 25%, 11%,and 37% (v/v), respectively. Thus, P. clematidea could be used as an A. gangetica weed biocontrol agent and might be integrated into weed management programs.